1993
DOI: 10.1007/bf02047382
|View full text |Cite
|
Sign up to set email alerts
|

Influence of suture physicochemical and surface topographic structure on tumor cell adherence

Abstract: Local recurrence following curative resection for colorectal cancer may be caused by the seeding of free malignant cells at the anastomotic site. This study investigated the influence of suture material on in vitro tumor cell adherence. Radiolabeled rat colonic cancer cells (RCC5) were incubated with a variety of suture materials, and the relative contribution of chemical composition and physical configuration to cell adherence was assessed. Nonadherent cells were washed free, and the cell adherence was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This, coupled with relatively low rate of cell migration from the suture to plastic, suggests Ethiobond sutures provided a better surface for cell attachment in vitro. Multifilament sutures have been shown to be better surfaces for cell adhesion, 26 and this can probably be attributed to their patterned surface with ridges and grooves, ideal for cell adherence and alignment. 27 The braided nature of Ethibond has also been linked to excellent mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, coupled with relatively low rate of cell migration from the suture to plastic, suggests Ethiobond sutures provided a better surface for cell attachment in vitro. Multifilament sutures have been shown to be better surfaces for cell adhesion, 26 and this can probably be attributed to their patterned surface with ridges and grooves, ideal for cell adherence and alignment. 27 The braided nature of Ethibond has also been linked to excellent mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to relatively weak cell adhesion and spread on this smooth suture, as seen in the fluorescence images. In past studies, PDSII has been shown to have low cell adhesion rates of rat colonic cancer cells compared to other sutures 26 but good tissue engineering results using bone marrow cells. 39 There is little previous information on its interaction with tendon-derived cells.…”
Section: Figurementioning
confidence: 98%
“…No adjuvant therapy was recommended for patients with stage I rectal tumours (Dukes A), although patients with stage I1 and 111 tumours (Dukes B and C) should receive 5-FU or methyl-N-(2-chloroethy1)-N-cyclo-hexyl-N-nitrosourea (methyl-CCNU) and high-dose pelvic irradiation (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Adjuvant Therapyh"mentioning
confidence: 99%
“…In April 1990 the NIH Consensus Development Conference produced a statement relating to adjuvant therapy for patients with colon and rectal In addition to recommending the adoption of the TNM system for staging colorectal cancer, they suggested that, based on 'high-quality studies', stage 111 patients (Dukes C) with colon cancer unable to enter a clinical trial should be offered 5-fluorouracil (5-FU) and levamisol, but they did not recommend specific adjuvant therapy for patients with stage I or stage I1 disease (Dukes A and B). No adjuvant therapy was recommended for patients with stage I rectal tumours (Dukes A), although patients with stage I1 and 111 tumours (Dukes B and C) should receive 5-FU or methyl-N-(2-chloroethy1)-N-cyclo-hexyl-N-nitrosourea (methyl-CCNU) and high-dose pelvic irradiation (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Adjuvant Therapyh"mentioning
confidence: 99%